The princess and the pea: Favourite tales - Andersen, Hans Christian; Baxter, Nicola Ayton, Robert (Ladybird Loughborough, 1993)
This is part of the "Favourite Tales" series which aims to bring alive classic fairy tales and folk stories from around the world. This book tells the story of the princess and the pea, originally by Hans Christian Andersen.